Aspirin and clopidogrel high on‐treatment platelet reactivity and genetic predictors in peripheral arterial disease - Yeo, Khung‐Keong; Armstrong, Ehrin J.; López, Javier E.; Chen, Debbie C.; Westin, Gregory G.; Li, Chin‐Shang; Anderson, David; Hua, Amy; Singapuri, Anil; Amsterdam, Ezra A.; Chiamvimonvat, Nipavan; Laird, John R. (Catheterization and cardiovascular interventions, 2018)
Objectives Our aims were to examine the prevalence and genetic predictors of aspirin and clopidogrel high on‐treatment platelet reactivity (HoTPR), and associated adverse cardiovascular outcomes in patients with peripheral arterial disease (PAD). Background The association of aspirin and clopidogrel HoTPR with outcomes in PAD remains unclear. Methods This is a prospective cohort study of patients with angiographically documented PAD involving carotid and lower extremity arteries. Aspirin and clopidogrel HoTPR (using the VerifyNow Assay) and associated genetic predictors were compared to clinical outcomes. The primary end‐point was a composite of major adverse cardiovascular events: all‐cause mortality, myocardial infarction, stroke, target vessel revascularization (TVR) and limb‐loss in patients who underwent extremity intervention. Results The study was stopped prematurely due to slow patient enrolment. Of 195 patients enrolled, the primary analysis was performed in 154 patients taking both drugs. Aspirin HoTPR was present in 31 (20%) and clopidogrel HoTPR in 76 (49%) patients. There was a trend toward more primary composite outcome events with PRU ≥ 235 (52% freedom‐from‐event rate vs. 70% for PRU < 235; P = 0.09). TVR was higher in those with PRU ≥ 235 (20 vs. 6%, unadjusted P = 0.02). There was no association between aspirin HoTPR and combined outcomes. Single nucleotide polymorphisms in serum paraoxonase/arylesterase 1 (PON1) gene was associated with aspirin HoTPR (P = 0.005) while SNP in phospholipase A2, group III (PLA2G3) gene was associated with clopidogrel HoTPR (P = 0.002). Conclusion Clopidogrel HoTPR was significantly associated with TVR, while aspirin HoTPR was not associated with adverse clinical outcomes in patients with PAD.